The Impact of Fluctuations in Crude Oil Prices on Non-oil Exports in the Kingdom of Saudi Arabia - Elghawy, Hala (The Arab Journal of Administration, 2020)
Using annual data covering the period from 2000 to 2018, the effect of volatility in the price of crude oil on non-Saudi exports was estimated. Both the export sectors were from manufacturing industries, agricultural exports, as well as high-tech exports to represent non-oil exports. The study followed the application of the ARDL model to study the equilibrium relationship between the volatility in oil prices and the three export sectors. The results indicated that the manufacturing sector exports is the sector most affected by fluctuation in the price of oil, while the results did not indicate a long-term balance relationship through which the agricultural export sectors or high-tech products are affected by the change in oil prices. The study recommends the necessity of increasing investments in these two sectors in order to secure a stable export outcome to ensure stable economic growth rates for the Kingdom.